Reward Responsiveness in Patients with Opioid Use Disorder on Opioid Agonist Treatment: Role of Comorbid Chronic Pain. Issue 9 (24th February 2021) - Finan, Patrick H; Letzen, Janelle; Epstein, David H; Mun, Chung Jung; Stull, Samuel; Kowalczyk, William J; Agage, Daniel; Phillips, Karran A; Pizzagalli, Diego A; Preston, Kenzie L
Abstract: Objective: Evidence suggests that blunted reward responsiveness may account for poor clinical outcomes in both opioid use disorder (OUD) and chronic pain. Understanding how individuals with OUD and comorbid chronic pain (OUD+CP) respond to rewards is, therefore, of clinical interest because it may reveal a potential point of behavioral intervention. Methods: Patients with OUD (n = 28) and OUD+CP (n = 19) on opioid agonist treatment were compared on: 1) the Probabilistic Reward Task (an objective behavioral measure of reward response bias) and 2) ecological momentary assessment of affective responses to pleasurable events. Results: Both the OUD and the OUD+CP groups evidenced an increase in reward response bias in the Probabilistic Reward Task. The rate of change in response bias across blocks was statistically significant in the OUD group ( B = 0.06, standard error [SE] = 0.02, t = 3.92, P < 0.001, 95% confidence interval [CI]: 0.03 to 0.09) but not in the OUD+CP group ( B = 0.03, SE = 0.02, t = 1.90, P = 0.07, 95% CI: −0.002 to 0.07). However, groups did not significantly differ in the rate of change in response bias across blocks ( B = 0.03, SE = 0.02, t = 1.21, P = 0.23, 95% CI: −0.02 to 0.07). Groups did not significantly differ on state measures of reward responsiveness ( P' s ≥0.50). Conclusions: Overall, findings across objective and subjective measures were mixed, necessitating follow-up with a larger sample. The results suggest that although there is a reward response bias in patients with OUD+CP treated with opioid agonist treatment relative to patients with OUD without CP, it is modest and does not appear to translate into patients' responses to rewarding events as they unfold in daily life.